2010
DOI: 10.1159/000320601
|View full text |Cite
|
Sign up to set email alerts
|

Two Cases of Endogenous Endophthalmitis Caused by Gram-Positive Bacteria with Good Visual Outcome

Abstract: Background: Endogenous endophthalmitis is a rare disease and its visual prognosis is poor. Case Reports: We present two patients, a 60-year-old man and a 53-year-old man, who developed endogenous endophthalmitis caused byGram-positive organismsbut recovered good vision after antibiotics and vitrectomy. Results: The first patient complained of ocular pain and visual decrease in his right eye. Ophthalmoscopy showed inflammation in the anterior chamber and vitreous opacities. Antibiotic was administrated systemic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 7 publications
1
15
0
Order By: Relevance
“…Yoon et al 20 reported that the retina remained attached in all cases, and CF or better visual acuity was attained in half of the cases after early vitrectomy for endogenous endophthalmitis. Itoh et al 26 reported good visual outcome despite delayed surgical treatment. In our study, vitrectomy was done in 23 cases (43.1%) and visual acuity more than CFs was seen in 11 cases in the vitrectomy group.…”
Section: Discussionmentioning
confidence: 98%
“…Yoon et al 20 reported that the retina remained attached in all cases, and CF or better visual acuity was attained in half of the cases after early vitrectomy for endogenous endophthalmitis. Itoh et al 26 reported good visual outcome despite delayed surgical treatment. In our study, vitrectomy was done in 23 cases (43.1%) and visual acuity more than CFs was seen in 11 cases in the vitrectomy group.…”
Section: Discussionmentioning
confidence: 98%
“…There are studies in favor of early vitrectomy. [21][22][23][24] However, the benefit could not be replicated in other studies. 1,25 In this regard, we advocate early vitrectomy for patients with poor visual prognostic indicators especially the presence of hypopyon, which is independently associated with a higher rate of evisceration in this study.…”
Section: Management Recommendationsmentioning
confidence: 94%
“…This is well above the percentage of patients reported with similar improvement before this study [ 11 ]. Itoh et al also reported that early aggressive treatment can lead to good visual outcomes [ 89 ]. Early vitrectomy within 2 weeks of presentation, especially in severe cases or when suspecting a highly virulent organism, can lead to a good overall outcome [ 79 , 82 , 83 , 86 , 90 ].…”
Section: Reviewmentioning
confidence: 99%